Sinus of Valsalva aneurysm repairs: Operative technique and lessons learned. Issue 6 (6th April 2019) - Wingo, Matthew; de Angelis, Paolo; Worku, Berhane M.; Leonard, Jeremy R.; Khan, Faiza M.; Hameed, Irbaz; Lau, Christopher; Gaudino, Mario; Girardi, Leonard N.
Abstract: Objective: Sinus of Valsalva (SOV) aneurysms are rare and data on operative management are limited. They can cause right ventricular outflow tract or pulmonary artery compression, and rupture may be fatal. In this study, we describe our experience with the repair of 13 SOV aneurysms. Methods: All patients who underwent SOV aneurysm repair from May 2001 to December 2017 at our single tertiary referral center were reviewed retrospectively. Results: Thirteen patients (92% male) with a mean age of 60 years underwent repair of an SOV aneurysm; mean aneurysm diameter was 5.9 ± 0.8 cm and four patients (30.7%) presented with rupture into another cardiac chamber. Operative interventions included six Bentall procedures, five patch repairs (one with aortic valve replacement [AVR]), and two primary aneurysm closures both with concomitant AVR. There were no strokes, myocardial infarctions, re‐explorations, or deaths in the postoperative period. After an average of 2.25 years, computed tomographic imaging in five patients demonstrated no aneurysm recurrence. Conclusions: Surgery is a safe option for both ruptured and nonruptured SOV aneurysms. A variety of repair strategies may be used. Larger studies are needed.